Literasi keuangan syariah bagi generasi muda penerus ‎bangsa di SDN 3 Sedayu - Niswatin, Khoirun (Maliki Interdisciplinary Journal, 2023)
This Islamic financial literacy socialization activity is an effort to educate Islamic finance to elementary school-age children in the SDN 3 Sedayu environment, Turen District, Regency. From various studies that have been conducted, knowledge regarding Islamic financial literacy in the younger generation is still minimal and not optimal, therefore it is important to carry out socialization to increase literacy among the younger generation which can be started from an early age. Indonesia is currently intensively making many efforts to develop the Islamic economy, including the merger of Bank Mandiri Syariah, Bank BRI Syariah Tbk, and Bank BNI Syariah to become Bank Syariah Indonesia (BSI). The research method used is the Asset Based Community Development (ABCD) method. When the socialization was carried out the students seemed enthusiastic and active during the socialization and some of them wanted to be part of the future development of Indonesian Islamic finance. The results of the research conducted show that Islamic financial literacy at SDN 3 Sedayu is quite good, this can be seen from the activeness of students during socialization, but it also needs to be improved.